2011
DOI: 10.1016/j.firesaf.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model based on radiative heating for the determination of safety distances for wildland fires

Abstract: The radiative heat transfer is often the main thermal impact of a wildfire on people fighting the fire or on structures. Thus, the estimation of the radiation coming from the fire font and hitting a target is of primary importance for forest and urban managers. A new flame model based on the solid flame assumption is developed by considering a finite fire front width. The realistic description of finite fire front widths allows proposing a new criterion for the estimation of the radiative impact of the fire, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 23 publications
2
67
0
Order By: Relevance
“…These values are generally higher than the values predicted for safety zones using the physically based models. However, at flame heights exceeding 10 m, for all combinations of fire shelter use and probability level, the required SDFH ratios decrease and eventually become lower than Butler and Cohen's (1998a) model but similar to the models proposed by Zárate et al (2008) and Rossi et al (2011), generally ranging from 1 to 4 times the flame height.…”
Section: Fatal Injury Model (Survival Zone Separation Distance)supporting
confidence: 62%
See 3 more Smart Citations
“…These values are generally higher than the values predicted for safety zones using the physically based models. However, at flame heights exceeding 10 m, for all combinations of fire shelter use and probability level, the required SDFH ratios decrease and eventually become lower than Butler and Cohen's (1998a) model but similar to the models proposed by Zárate et al (2008) and Rossi et al (2011), generally ranging from 1 to 4 times the flame height.…”
Section: Fatal Injury Model (Survival Zone Separation Distance)supporting
confidence: 62%
“…Slope steepness has been reasoned as a potential contributor to safety zone size (Rossi et al 2011;Butler 2014b) as it is well recognised in aiding convective and radiative heat transfer and thus forward rate of spread (Rothermel 1972;Van Wagner 1977;Dupuy and Maréchal 2011). Here, we found that the probability of a fatal injury was directly related to slope steepness, where for each percentage point increase in slope, the odds of a fatal injury increased by 3%.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Forest fires causes a significant damage to ecology and economy of many countries [1,2]. Forest fires are harmful to the environment -from emissions of combustion products into the atmosphere to the complete destruction of vegetation cover over a large area.…”
Section: Introductionmentioning
confidence: 99%